The European Union Market as a Business Environment - Korolevych, Veronika (Lesya Ukrainka Volyn National University, 2024)
The common market is one of the forms of international economic integration, which provides for the free movement (trade) between the states that established it, of goods, services and factors of production. Having established free trade area with the EU today Ukraine in the future will become part of the EU common market, which makes it an interesting and important object of study. The foundations of the EU's single market are formed by four principles: the free movement of goods, persons, services and capital within the Union. It is by ensuring the fulfillment of these freedoms that significant gains in the single market have been possible. Among them, the most notable are additional economic growth, growth of living standards and employment, improvement of business opportunities, increase in competitiveness and investment attractiveness of the economy. The full-scale aggression of the Russian Federation in Ukraine, oddly enough, has created the best prerequisites for the presence of Ukrainian business in the EU market and the strengthening of trade and economic ties between Ukraine and the EU. The reasons for this were the abolition by the EU of a number of restrictions allowed for application by the Association Agreement, and providing our country with access to a whole range of EU programs and sectoral markets in order to support Ukraine in its confrontation with the Russian aggressor. Our state and business have been granted economic, transport, customs, energy, and digital «visa-free regimes». The political context for strengthening business relations was created by the Association Agreement, granting Ukraine the status of a candidate country, the start of negotiations on joining the EU, the provision of macro-financial, technical, military support by the EU to Ukraine.
Keywords: market; EU; Ukraine; business; four freedoms; commodity; trade; service; capital; workforce